Influência das distorções harmônicas na proteção de bancos de capacitores - Henrique Lopes dos Santos (2010)
The increase of circulation of harmonic voltages and currents in the electrical system is responsible for many problems in its performance, since great part of this system was de-signed in the past considering only the fundamental frequency. The protection of shunt capa-citor banks is also not immune to this power system quality deterioration. The sensitivity of neutral unbalance relay protection schemes for grounded wye capacitor banks is being re-duced in some substations to avoid false trips due to interference of harmonics in the neutral current. Thus, these protections are working in a precarious way, as the rise of their trip le-vels becomes them incapable to detect small failures. Therefore, this work verifies the preca-riousness of this type of protection and analyzes the performance of other three schemes: Compensated Neutral Current, Differential Voltage and Impedance. For this, digital simula-tions based on values of voltage and current measured in a 138 kV substation were done. To-gether with them, measurements were realized in a reduced model of a capacitor bank, which considered, in laboratory, high taxes of harmonic distortion and inherent capacitor bank and system unbalances. In this manner, it was possible to determine the tougher protection scheme and the one that presents the best sensitivity for small failures in these conditions.